2013
DOI: 10.1080/00268976.2013.818728
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical estimation of the aqueous pKas of thiols

Abstract: The ionisation state of a compound is a key parameter influencing the compound's activity as a drug, metabolite, pollutant, or other active chemical agent. Sulfhydrol compounds (thiols) tend to be considerably more acidic than their hydroxyl (alcohol) analogues. In this report, quantum chemical approaches previously used for the estimation of the aqueous pK a s of alcohols are applied to the estimation of the acidities of thiols. Acidity estimates obtained from the general-purpose SPARC calculational programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…91,309,316,318,323,344 In most of these studies, RM1 was used to obtain the ground state geometries and other molecular properties, either in gas phase, or in solution (using any solvation model). In the following studies, RM1 displayed good performance: (i) in reproducing circular dichroism (CD) spectra for (M)-hexahelicene and in giving experimentally consistent results for reduced rotational strengths of cyclohexanones, 324 (ii) in being consistent with experimental data for aqueous pK a of 48 sulfhydrol compounds (thiols) by using SM5.4 and SM8 solvent models 322 and (iii) in giving low overal mean absolute error (MAE) for Δ r H (enthalpy of reaction) of 34 isomerization reactions of 4.2 kcal mol -1 and ∆ f H of 1356 molecules, radicals, ions, and complexes (MAE of 5.0 kcal mol -1 ). 343 Nonetheless, some studies also pointed out certain RM1 failures, such as: (i) inability to describe the interaction of small organic molecules with graphene; 321 (ii) wrong prediction of planar configurations for both the ground and singlet states for trans-stilbene; 330 (iii) overestimation of cis-trans isomerization energy and ionization potential of both cis-and trans-stilbene; 330 and (iv) larger errors in describing cysteine-histidine proton transfer at aqueous media with the COSMO implicit solvent model.…”
Section: Comparison Studiesmentioning
confidence: 71%
See 1 more Smart Citation
“…91,309,316,318,323,344 In most of these studies, RM1 was used to obtain the ground state geometries and other molecular properties, either in gas phase, or in solution (using any solvation model). In the following studies, RM1 displayed good performance: (i) in reproducing circular dichroism (CD) spectra for (M)-hexahelicene and in giving experimentally consistent results for reduced rotational strengths of cyclohexanones, 324 (ii) in being consistent with experimental data for aqueous pK a of 48 sulfhydrol compounds (thiols) by using SM5.4 and SM8 solvent models 322 and (iii) in giving low overal mean absolute error (MAE) for Δ r H (enthalpy of reaction) of 34 isomerization reactions of 4.2 kcal mol -1 and ∆ f H of 1356 molecules, radicals, ions, and complexes (MAE of 5.0 kcal mol -1 ). 343 Nonetheless, some studies also pointed out certain RM1 failures, such as: (i) inability to describe the interaction of small organic molecules with graphene; 321 (ii) wrong prediction of planar configurations for both the ground and singlet states for trans-stilbene; 330 (iii) overestimation of cis-trans isomerization energy and ionization potential of both cis-and trans-stilbene; 330 and (iv) larger errors in describing cysteine-histidine proton transfer at aqueous media with the COSMO implicit solvent model.…”
Section: Comparison Studiesmentioning
confidence: 71%
“…328 A benchmark investigation involving RM1 and DFT methods was also performed in the estimation of the aqueous pK a s of a set of thiols. 322 In this work, Hunter and Seybold 322 concluded: "Perhaps surprisingly, the semiempirical RM1 computational method provided comparable results to the SPARC and ACD benchmark calculations in estimating the pK a s for the complete set. Before application of the SM8 solvent model, the more demanding DFT B3LYP/6-31+G* calculations not only did not offer any advantage over the RM1 calculations but also gave poorer results".…”
Section: Comparison Studiesmentioning
confidence: 86%
“…55,56 Alternatively, in terms of arguments based on heterolytic bond dissociation energies, electron-withdrawing substituents weaken Cd–SAr bonds to a smaller degree than they do for H–SAr bonds. 57−59 …”
Section: Resultsmentioning
confidence: 99%
“…The thermodynamics of the cadmium thiolate exchange reactions are dictated by the differential effect of the substituent on the Cd–SAr and H–SAr bond energies. On the basis of the aforementioned zinc alkoxide study, the observed thermodynamic trend can be rationalized by electron-withdrawing substituents increasing the Cd–SAr bond dissociation energies to a greater degree than the H–SAr bond dissociation energies. , Alternatively, in terms of arguments based on heterolytic bond dissociation energies, electron-withdrawing substituents weaken Cd–SAr bonds to a smaller degree than they do for H–SAr bonds. …”
Section: Resultsmentioning
confidence: 99%
“…For the studies in aqueous solution, the SM8 aqueous solvent model of Marenich et al [41,42] was used. This same solvent model was also employed in our earlier study of purines and indoles [11] and other studies [16,17,43], where it was shown to perform well in helping to reproduce the experimental data.…”
Section: Methodsmentioning
confidence: 99%